Positive and Negative Factors in International Electricity Integration - Fedosova, Alina (International Journal of Energy Economics and Policy, 2015)
The article provides a review of international experience in the field of electricity markets integration in Central American countries and EPEX SPOT zone. The revision of earlier results for Nord Pool, NAFTA and MERCOSUR is given. Conclusions about common positive and negative factors affecting the process of integration are derived. Keywords: Electricity, Integration, Regional markets, Cross-border trading JEL Classifications: O240; R110